Association of intraventricular hemorrhage secondary to prematurity with cerebrospinal fluid shunt surgery in the first year following initial shunt placement - Simon, Tamara D. (2012)
OBJECT: The neurosurgical literature has conflicting findings regarding the association between indications for CSF shunt placement and subsequent shunt surgery. The object of this study was to identify baseline factors at the time of initial CSF shunt placement that are independently associated with subsequent surgery. METHODS: This was a retrospective cohort study of children ages 0–18 years who underwent initial CSF shunt placement between January 1, 1997, and October 12, 2006, at a tertiary care children’s hospital. The outcome of interest was CSF shunt surgery (either for revision or infection) within 12 months after initial placement. Associations between subsequent CSF shunt surgery and indication for the initial shunt, adjusting for patient age and surgeon factors at the time of initial placement, were estimated using multivariate logistic regression. Medical and surgical decisions, which varied according to surgeon, were examined separately in a univariate analysis. RESULTS: Of the 554 children in the study cohort, 233 (42%) underwent subsequent CSF shunt surgery, either for revision (167 patients [30%]) or infection (66 patients [12%]). In multivariate logistic regression modeling, significant risk factors for subsequent CSF shunt surgery included (compared with aqueductal stenosis) intraventricular hemorrhage (IVH) secondary to prematurity (adjusted odds ratio [AOR] 2.2, 95% CI 1.1–4.5) and other unusual indications (AOR 3.7, 95% CI 1.0–13.6). The patient’s age at initial CSF shunt placement was not significantly associated with increased odds of subsequent surgery after adjusting for other associated factors. CONCLUSIONS: The occurrence of IVH is associated with increased odds of subsequent CSF shunt surgery within 12 months after shunt placement. Families of and care providers for children with IVH should be attuned to their increased risk of shunt failure.